Scaled Fracture Toughness Based on the Weibull Stress for the Ferritic Steel Used in Nuclear Power Plants - Jin, Weiya; Li, Yan; Li, Yuebing; Zhou, Mingjue (Frontiers in Materials, 2022)
As an important material property in structural integrity assessment of nuclear power components, fracture toughness can be measured by single edge-notched bend (SENB) specimens or compact tension (CT) specimens. However, the tested values may be inhomogeneous with the crack size and specimen thickness. Some toughness scaling models (TSMs) were proposed to transfer the tested value to fracture toughness under small-scale yielding. Combined with the tested data by SENB specimens with different crack sizes and CT specimens with different thicknesses, the scaled fracture toughness is investigated on the global and local approaches to fracture. Using the scaled toughness values, the Weibull scale parameter K0 is estimated and compared for the ferritic steel DIN 22NiMoCr37 widely used in nuclear power plants. The results show that the estimated scale parameter K0 using the scaled toughness obtained by the global approach on the J-Q theory is reasonable in agreement with that of the local approach on the Weibull stress with a relative error of about 10%.